Statistical analysis of the scientific potential of the Russian Federation regions - M. R. Efimova (Publishing House of the State University of Management, 2019)
The main indicators, characterizing the scientific potential of the regions of the Russian Federation, have been considered. The distribution of organizations, performing research and development, as well as personnel employed in them, by region, has been analyzed. Particular attention has been paid to the characteristics of the scope of variation and uniformity of the number of personnel per organization, engaged in research and development in the subjects of the Russian Federation. The analysis of the availability of academic degrees of candidate and doctor of sciences in scientific personnel in the regions of the country has been made. Attention to the assessment of the dynamics of the number of organizations, training postgraduate and doctoral students, has been paid.